The Effect of Group Counseling Services on the Dangers of Narcolema Among Adolescents Using the Self-Control Technique - Miranda, Ivo Liza; Siregar, Alfin (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study aims to evaluate the impact of group counseling services using self-control techniques on the dangers of narcolema (pornography addiction) among adolescents. The issue addressed is the high level of pornography addiction among teenagers, which poses significant risks to their physical, mental, and social well-being. The research utilized a quantitative approach with a